ナンキョクテン ゼンテン サツゾウ ソウチ ノ ガイヨウ ト ショキ データ カイセキ - 岡田, 雅樹; オカダ, マサキ; 江尻, 全機; エジリ, マサキ; 岡野, 章一; オカノ, ショウイチ; 田口, 真; タグチ, マコト; 竹下, 秀; タケシタ, シュウ; Okada, Masaki; Ejiri, Masaki; et al. (1997)
P(論文) われわれは高感度全天撮像装置(ASI : All-sky optical imager)の開発を行い, 1996年から1997年の南半球夏期間において, 南極点基地(South Pole Station; SP)に同カメラを設置した。ASIは, 高感度(モノクロおよびパンクロ)の光学レンズ系およびCCDカメラ部, およびデータ取得用ワークステーション部(WS)から構成される。光学系のフィルターとして, N_2^+ 427.8nm, およびOl 557.7nm, OI 630.0nm, OH730.0nmのフィルターを装備している。WS部はインターネットを介して国立極地研究所より制御され, 全データはデジタルリニアテープに記録される一方, 一部のデータはインターネットを使って国立極地研究所に電送される。本論文では, システム構成およびデータフォーマットの詳細についてまとめるとともに, 初期データの解析結果について述べる。 We have developed an all-sky optical imager (ASI) which was installed at the Amundsen-Scott South Pole Station (SP) in the 1996-1997 austral summer season. ASI consists of a highly sensitive (monochromatic and panchromatic) optical lens, CCD camera, and a data-taking workstation. The ASI is equipped with interference filters of N_2^+ 427.8nm, Ol 630.0nm, and OH 730.0nm. The image sensor is a back-illuminated air-cooled CCD camera with 512×512 pixels. The size of each pixel is 24μm×24μm. The workstation (WS) is controlled from NIPR via the internet and stores the image data to a digital linear tape (DLT) drive. Selected image data can be sent to NIPR via the Internet during the observational period. We present the detailed system configuration, the data formats and the initial images taken by the ASI-SP system. departmental bulletin paper